Use of Student Worksheets) in Increasing Learning Motivation in Social Studies Learning - Komala, Kokom; Sutisna, Deni; Noprihaldi Rohman , Slamet; Mustikarani, Wini (SAHUR Journal, 2023)
Education is the process of transferring values in a society to each individual in it and the process of transferring cultural values through teaching. Socio-cultural changes are very fast and touch changes in value systems, so that they have an impact on the intensity of socio-cultural problems. The research approach uses quantitative research with a quasi-experimental design type, and the research design uses a nonequivalent control group design. Then use the purposeful sampling technique, or judgmental sampling. Research data collection techniques using tests identified through pretests and posttests and non-tests through observation, interviews, and documentation studies Data validation analysis techniques use validity tests, normality tests, homogeneity tests, hypothesis tests, and normalized gain tests. The results of the study show that (1) it can be identified before using the LKPD that there is no significant difference in the pre-test results between the experimental class and the control class before learning begins. (2) There are significant differences in pretest results between the experimental class and the control class before learning begins. (3) The attitude of students towards the application of student worksheets in general shows a very good attitude, and the attitude of students towards the application of student worksheets for everyone shows a very good attitude and influences the increase in student motivation. Thus, LKPD-based learning plays a role in supporting the increase in learning motivation in students.